The impact of board governance effectiveness on carbon disclosure in the banking sector - Mansour, Marwan; Albawwat, Ala; Marei, Ahmad; Mujahed, Murad; Nofal, Mohammed (Llc Cpc Business Perspectives, 2026)
Climate-related risks have intensified the demand for transparency in the banking sec-tor, particularly with respect to carbon-related information disclosed to stakeholders. In emerging economies, where climate disclosure remains largely voluntary, internal governance mechanisms are expected to play a decisive role in shaping reporting prac-tices. The aim of this study is to examine the relationship between board governance effectiveness and carbon emission disclosure in the ASEAN banking sector. The object of the study is listed commercial banks operating in six ASEAN countries over the period 2014–2023. The analysis is based on panel data and employs fixed-effects and Tobit regression models to account for unobserved heterogeneity and the bounded nature of disclosure scores. The results indicate that board governance effectiveness is positively and statistically associated with carbon emission disclosure. Accordingly, the within R-squared value for the fixed-effects model is 23.5%, while the pseudo R-squared for the Tobit model is 55%, indicating strong explanatory power of both specifications. Economically, a one-point increase in the Board Effectiveness Score corresponds to an increase of 2.630 units in carbon emission disclosure in the fixed-effects model and 4.550 units in the Tobit specification, indicating economically meaningful improve-ments in disclosure intensity. In addition, bank size, age, profitability, and eco-innovation activity are found to be positively related to disclosure levels. The results remain robust across alternative specifications, including panel quantile regression, panel logit estimation, and two-step system generalized method of moments.